Ottoman Provincial Organization and Its Development in the 16th Century as Traceable in the Ruus Registers - (:unkn) unknown (ISAM, 2011)
This study, which examines the appointment records of various administrators who were members of the Province Beylerbeyi and the Province consul (Eyalet Divan, firstly provides information regarding the development of the Province organisation and also relating to the beylerbeylik system. After that, based on the ruus registers of the sixteenth century as a basis, the appointment records collected from these registers are evaluated. The study examines 47 registers covering the years 954-1001, the appointments of the administrators have been identified and the transcriptions of these documents have been arranged in alphabetical and chronological order. The appointment records of the Province beylerbeyi have been listed first, followed by the appointment records of the timar defterdarlari, the timar tezkirecileri, the timar defter eminleri, the dinar kethudalari, the defter kethudalari, the defter eminleri, the tezkire eminleri. The appointment records relating to the province administrators include very important information and they help scholars to correct some facts. The records help scholars and researches to clarify system of provinces administration and the form of province administrators.
Keywords: Ottoman Provinces; Province Beylerbeyi; Province consul; ruus registers; appointment records